Commentary: An Arctic Institute for the New Millennium - Robinson, Mike (ARCTIC, 1995)
In this commentary, the Director of the Arctic Institute, Mike Robinson, discusses the present and future prospects of the Institute including Arctic, ASTIS, Kluane Research Station and professional services contacts.